Liability of Business Actors for the Protection of Consumer Personal Data - Hasan, Fuad (Faculty of Law, Mulawarman University, 2024)
The Consumer Protection Law does not expressively verbis state the protection of consumer personal data as part of consumer rights that must be protected by business actors. The existence of cybercrime and the negligence of business actors can cause leakage of consumer personal data to be something that needs to be anticipated. This paper aims to discuss the application of the PDP Law to consumer protection of personal data and how the form of liability of business actors in the perspective of the PDP Law in ensuring consumer protection. This paper uses normative research with a conceptual approach, a statutory approach, and a case approach. This paper also concluded that The handling of consumer disputes related to personal data breaches should be handled in parallel by applying the PDP Law and the Consumer Protection Law. Business actors should protect consumers' personal data based on the provisions prohibiting disclosing personal data unlawfully. The application of the principle of absolute accountability or strict liability is intended so that business actors can be fully responsible for the interests of consumers. In the event that there is negligence on the part of the business actor, resulting in a violation of the protection of consumers' personal data. Business actors cannot escape responsibility for any reason because they have neglected to protect consumers' personal data.